2015
DOI: 10.3390/s150922941
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Impedance Spectroscopy-Based Technique to Identify and Quantify Fermentable Sugars in Pineapple Waste Valorization for Bioethanol Production

Abstract: Electrochemical Impedance Spectroscopy (EIS) has been used to develop a methodology able to identify and quantify fermentable sugars present in the enzymatic hydrolysis phase of second-generation bioethanol production from pineapple waste. Thus, a low-cost non-destructive system consisting of a stainless double needle electrode associated to an electronic equipment that allows the implementation of EIS was developed. In order to validate the system, different concentrations of glucose, fructose and sucrose wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The dry matter content of pineapple waste is around 10%, composed of about 96% organic matter and 4% inorganic matter (Abdullah, 2007). According to (Conesa et al, 2015), in the elaboration of pineapplebased food products, this value can be 50%. Other authors reported a waste production from pineapples processing in the range of 25-35% of the weight of the fruit (Seleni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The dry matter content of pineapple waste is around 10%, composed of about 96% organic matter and 4% inorganic matter (Abdullah, 2007). According to (Conesa et al, 2015), in the elaboration of pineapplebased food products, this value can be 50%. Other authors reported a waste production from pineapples processing in the range of 25-35% of the weight of the fruit (Seleni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…EIS measurements were carried out using a measurement system developed by the Group of Electronic Development and Printed Sensors (GED+PS) belonging to the Centro de Reconocimiento Molecular y Desarrollo Tecnológico (IDM) at the Universitat Politècnica de València (UPV). This system consists of a device called Advanced Voltammetry, Impedance Spectroscopy & Potentiometry Analyzer (AVISPA) associated to a specific software application that is able to apply different sinusoidal voltage signals with amplitudes up to 1 Vpp and frequency sweep from 0.01 Hz to 10 MHz using up to 32 current scales [ 38 ]. It means that the frequency range, the number of the sweep frequencies, the current scale and the amplitude of the sine wave applied to the sensor can be completely configured by means of the software.…”
Section: Methodsmentioning
confidence: 99%
“…The applied sensor was the same as the one previously used in the identification and quantification of sugars added to pineapple waste [ 38 ], consisting of a 1.5 cm in length and 1 mm in diameter double needle electrode (working and counter electrodes) made of stainless steel and encapsulated in epoxy resin to assure a constant separation of 1 cm between the needles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, EIS is simple and immediate, does not require reagents or toxic compounds, and is also comparatively inexpensive. In the field of food technology, EIS has already been used in the evaluation of the physiological properties of kiwi fruit [12], the ripening of mango [13], the analysis of eggplant pulp [14], the differentiation between fresh and frozen-thawed sea bream [15], the control of properties in carrots [16,17], the analysis of the effect of temperature on potatoes [18], the study of the behavior of tomato skin [19], the use of pineapple waste for bioethanol production [20,21], and even in the control of steel corrosion by adding orange extracts [22].…”
Section: Introductionmentioning
confidence: 99%